Managing the Tide : How Do Emerging Markets Respond to Capital Flows? - Ghosh, Atish (IMF Working Papers; Working Paper ;, 2017)
This paper examines whether-and how-emerging market economies (EMEs) respond to capital flows to mitigate their untoward consequences. Based on a sample of about 50 EMEs over 2005Q1-2013Q4, we find that EME policy makers respond proactively to capital inflows by using a combination of policy tools: central banks raise the policy interest rate to address economic overheating concerns; intervene in the foreign exchange market to resist currency appreciation pressures; tighten macroprudential measures to dampen credit growth; and deploy capital inflow controls in the face of competitiveness and financial-stability concerns. Contrary to conventional policy advice to EMEs, we find no evidence of counter-cyclical fiscal policy in the face of capital inflows. Overall, policies are more likely to respond, and used in combination, during inflow surges than in more normal times.